Soekarno's Political Thingking About Guided Democracy - Argenti, Gili; Istiningdias, Dini Sri (Jurnal Politikom Indonesiana, 2018)
Soekarno is one of the leaders of the four founders of the Republic of Indonesia, his political thinking is very broad, one of his political thinking about democracy is guided democracy into controversy, in his youth Soekarno was known as a very revolutionary, humanist and progressive figure of political thinkers of his day. His thoughts on leading democracy put his figure as a leader judged authoritarian by his political opponents. This paper is a study of thought about Soekarno, especially his thinking about the concept of democracy which is considered as a political concept typical of Indonesian cultures. Key word: Soekarno, democracy